Membangun Karakter Kemandirian Anak Usia Dini Melalui Budaya Sekolah di BA Arafah Malang - Syarif, Safira Nurlita (Jurnal Penelitian Anak Usia Dini, 2023)
Building the character of independence from an early age is very important to train children to be able to do their own activities without involving others. So that it can also help children to survive in the future. Building the character of children's independence can be done through school culture. This study shows the success of the application of school culture in building the character of early childhood independence, namely at BA Arafat Malang. BA Arafah itself has several school cultures that are routinely carried out, namely through a culture of habituation, providing motivation, healthy / nutritious eating activities together and also pre-service activities. Some of these cultures have a good impact on children's development, especially on their independence as the success of the school culture, among others; children are able to carry out their activities independently, children become more active and enthusiastic, children become more courageous, confident, reduce children's dependence on their parents, and children find it difficult to leave various habits that are often done at school. ABSTRAK Membangun karakter kemandirian sejak usia dini sangat penting untuk melatih anak agar bisa melakukan aktivitasnya sendiri tanpa melibatkan orang lain. Sehingga hal tersebut juga dapat membantu anak agar bisa bertahan hidup pada masa mendatang. Membangun karakter kemandirian anak ini dapat dilakukan melalui budaya sekolah. Pada penelitian ini memperlihatkan keberhasilan dari penerapan budaya sekolah dalam membangunan karakter kemandirian anak usia dini yakni di BA Arafah Malang. BA Arafah sendiri memiliki beberapa budaya sekolah yang rutin dilakukan yaitu melalui budaya pembiasaan, pemberian motivasi, kegiatan makan sehat/bergizi bersama dan juga kegiatan prasiaga. Beberapa budaya tersebut membawa dampak yang baik bagi perkembangan anak terlebih pada kemandiriannya sebagai keberhasilan dari budaya sekolah tersebut antara lain; anak mampu untuk melakukan aktivitasnya secara mandiri, anak menjadi lebih aktif dan juga antusias, anak menjadi lebih berani, percaya diri, mengurangi ketergantungan anak terhadap orangtuanya, dan anak sulit untuk meninggalkan berbagai pembiasaan yang sering dilakukan disekolah.